2020
DOI: 10.21203/rs.3.rs-29151/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survey of the Patients' Satisfaction with Services provided in an Iranian Naval Hospital in 2019: A Cross-sectional Study

Abstract: Background All hospital services are carried out to serve the patient, which is the main axis in the hospital. Patient satisfaction can be indicative of the right performance service delivery and is considered as a reliable source for evaluating the quality of health care. the present study was conducted to evaluate the satisfaction rate of discharged patients in a Navy hospital. Methods The descriptive cross-sectional study was performed on 220 discharged patients who selected by convenience sampling in a N… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A meta-analysis confirmed that before the pandemic the quality of services stated by the Iranian patients was placed at an acceptable level compared to other countries [ 56 ]. In general, prior research reported varied results in Iran [ 57 61 ]. Such difference findings may be related to study settings, the time of the study, sample size, and the participants’ status in terms of socio-economics factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis confirmed that before the pandemic the quality of services stated by the Iranian patients was placed at an acceptable level compared to other countries [ 56 ]. In general, prior research reported varied results in Iran [ 57 61 ]. Such difference findings may be related to study settings, the time of the study, sample size, and the participants’ status in terms of socio-economics factors.…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, service quality can be measured in five dimensions: Tangibles (the appearance of physical facilities, equipment, personnel, and communication materials), Responsiveness (the willingness to help customers and to provide prompt service), Assurance (the knowledge and courtesy of employees and their ability to convey trust and confidence), Reliability (the ability to perform the promised service dependably and accurately), and Empathy (the provision of caring, individualized attention to the customer) are examined [53]. Regarding the quality of hospital services, the findings of previous studies before and after the outbreak of COVID-19 have reported different levels of service quality and its dimensions status [54][55][56][57][58][59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…Each question was confirmed if 50% of the patients chose either the first option or 70% chose the first two options. Therefore, face validity was also confirmed [14,15]. The Guttman split-half coefficient was used to evaluate the reliability and correlation coefficient: estimated r=0.9.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Patient satisfactions in terms of care received is one of the key areas in health globally. Patient satisfaction is very crucial in health as it helps to evaluate the services offered (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Optimum nursing care can be used to captured flaws in the health sectors because nursing act as a backbone of health as nurses play many roles in the field of health.…”
Section: Introductionmentioning
confidence: 99%